Outcomes Following Metabolic Bariatric Surgery at a Single Center in the United Arab Emirates - Allum M; Buckley A; Suliman SGI; Suliman M; Hamdan K; Al Hadad M (Diabetes, Metabolic Syndrome and Obesity)
Matthew Allum,1 Adam Buckley,1 Sara GI Suliman,1 Mohamed Suliman,1 Khaled Hamdan,2 Mohamed Al Hadad2 1Department of Endocrinology, Imperial College London Diabetes Centre, Abu Dhabi, United Arab Emirates; 2Department of Bariatric and Metabolic Surgery, Healthpoint Hospital, Abu Dhabi, United Arab EmiratesCorrespondence: Matthew Allum, Consultant Endocrinologist, Department of Endocrinology, Imperial College London Diabetes Centre, Abu Dhabi, PO Box 48338, United Arab Emirates, Tel +971 24040800, Email mallum@icldc.aeIntroduction: While the benefits of metabolic bariatric surgery (MBS) are well described, only few studies have been published from the Gulf region, where the impact of regional patient characteristics on outcomes remains poorly understood.Methods: Data were reviewed for patients attending metabolic follow-up three or more months after primary MBS at our center in the UAE from 2016 to 2022. Total weight loss (TWL), status of type 2 diabetes (T2D), hyperlipidemia, and hypertension were assessed following sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB).Results: Of 2851 included patients, 62.6% were female and 94.0% Emirati. Pre-operatively, mean age was 34.2 ± 0.2 years, median BMI was 41.0 (IQR 37.8– 45.2) kg/m2; 92.5% had SG and 7.5% RYGB. %TWL (95% confidence interval) for RYGB was 31.2% (30.0– 32.5), 30.9% (29.0– 32.9) and 28.4% (23.0– 33.8) at 1, 3 and 5 years. Following SG, %TWL was 29.9% (29.5– 30.3), 25.8% (25.0– 26.7) and 23.4% (21.6– 25.2) for the same intervals. The proportion of total operated patients included was 60.2%, 43.7% and 33.8% respectively. Men lost more weight than women 12 months after SG, with mean %TWL of 32.5% (31.8– 33.2) vs 28.4% (27.9– 28.9) respectively. T2D remission (HbA1c < 6.5% without diabetes medications) after SG was 61.9% (179/289) at 1 year and 40.9% (18/44) at 5 years. RYGB favored T2D remission over SG at 12 months, OR=2.272 (1.152– 4.65). There was no difference between procedures for hypertension status, although remission from hyperlipidemia was higher 1 year after RYGB at 41.8% (23/55) compared to SG 16.4% (78/475) (p< 0.001).Conclusion: In this young Emirati cohort, RYGB was associated with more weight loss and favored T2D and hyperlipidemia remission over SG. Women lost less weight than men after SG. Weight recurrence from 1 to 5 years after SG was greater than the international average. Further research is required to explain these differences and improve outcomes.Keywords: type 2 diabetes, Arab, total weight loss, weight recurrence, diabetes remission, metabolic surgery